NextLens—The Next Generation of Surgical Navigation: Proof of Concept of an Augmented Reality System for Surgical Navigation - Grunert, Ronny; Snyderman, Carl-Henry; Gardner, Paul; Busse, Michel; Ahner, Lukas; Kropla, Fabian; Möbius, Robert; Jung, Svenja; Scholz, Sebastian; Güresir, Erdem; Winkler, Dirk (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objective The aim of this work was the development of an augmented reality system including the functionality of conventional surgical navigation systems.Methods An application software for the Augmented Reality System HoloLens 2 from Microsoft was developed. It detects the position of the patient as well as position of surgical instruments in real time and displays it within the two-dimensional (2D) magnetic resonance imaging or computed tomography (CT) images. The surgical pointer instrument, including a pattern that is recognized by the HoloLens 2 sensors, was created with three-dimensional (3D) printing. The technical concept was demonstrated at a cadaver skull to identify anatomical landmarks.Results With the help of the HoloLens 2 and its sensors, the real-time position of the surgical pointer instrument could be shown. The position of the 3D-printed pointer with colored pattern could be recognized within 2D-CT images when stationary and in motion at a cadaver skull. Feasibility could be demonstrated for the clinical application of transsphenoidal pituitary surgery.Conclusion The HoloLens 2 has a high potential for use as a surgical navigation system. With subsequent studies, a further accuracy evaluation will be performed receiving valid data for comparison with conventional surgical navigation systems. In addition to transsphenoidal pituitary surgery, it could be also applied for other surgical disciplines.
Keywords: augmented reality; surgical navigation; transsphenoidal pituitary surgery; computer-assisted surgery